2002
DOI: 10.1046/j.0022-0477.2001.01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an affinity threshold for IgE‐allergen binding in the percutaneous skin test reaction

Abstract: The product of antibody affinity and concentration, which we define as antibody capacity (CAP = K(A) x IgE), is more informative with regard to describing allergen sensitivity than antibody concentration alone. Antibody binding capacity provides physiological evidence of atopy in some subjects who do not test positively by common methods and suggests an affinity threshold to produce a positive SPT reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 15 publications
4
27
0
Order By: Relevance
“…As previously shown [16, 17], interactions between IgE and purified allergens are complex, heterogeneous reactions. The total binding capacity is defined as: CAP ≡ [IgE] × Σ n i = 1 K i × p[K] i , where [IgE] is the specific IgE concentration, n is the number of specific reactions, K i is the equilibrium binding constant for the ith reaction and p[K] i is the relative proportionate amount of each reaction.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…As previously shown [16, 17], interactions between IgE and purified allergens are complex, heterogeneous reactions. The total binding capacity is defined as: CAP ≡ [IgE] × Σ n i = 1 K i × p[K] i , where [IgE] is the specific IgE concentration, n is the number of specific reactions, K i is the equilibrium binding constant for the ith reaction and p[K] i is the relative proportionate amount of each reaction.…”
Section: Resultsmentioning
confidence: 98%
“…On average, those with SPT-positive results have higher reaction binding affinities compared to those with SPT-negative results [17]. Independent investigators have shown that binding affinity is positively correlated with histamine release by basophils in vitro [24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From this perspective it is not surprising that monoglycosylated bromelain did not give positive skin tests in patients with IgE antibodies recognizing the glycan moiety of this glycoprotein [15]. Then, the affinity of the interaction between allergen and IgE also plays a role [70, 71]. High-affinity interactions seem to be needed for the triggering of effector cells.…”
Section: Clinical Relevance Of Ige Antibodies Against N-glycansmentioning
confidence: 99%